Innovation and Financial Disclosure - CHEN, HUI; LIANG, PIERRE JINGHONG; PETROV, EVGENY (Journal of accounting research, 2024)
ABSTRACT We examine how financial disclosure policy affects a firm manager's strategy to innovate within a two‐period bandit problem featuring two production methods: an old method with a known probability of success, and a new method with an unknown probability. Exploring the new method in the first period provides the manager with decision‐useful information for the second period, thus creating a real option that is unavailable under exploiting the old known production method. Voluntary disclosure of the firm's financial performance provides the manager with another option to potentially conceal initial failure from the market. The interaction of these two options determines the manager's incentive to explore. In equilibrium, a myopic manager who cares about the interim market price may over‐ or under‐explore compared to the optimal exploration strategy that maximizes firm value. Our analysis shows that firms operating in an environment with voluntary disclosure early in the trial stage and mandated requirement later are most motivated to explore, while firms subject to early mandated disclosure and late voluntary disclosure are least likely to do so. We also provide empirical predictions about the link between the disclosure environment and the intensity and efficiency of corporate innovation.